Sunnah Prayer And Sunnah Fasting On Increasing The Character Value Of Physical Education In Boarding Boards - Eko Yogaswara; Adang Sudrazat; Anggi Setia Lengkana (STKIP Muhammadiyah Kuningan, 2022)
Pesantren is an educational institution where to educate and gain knowledge, not only religious knowledge but must be able to form character based on the character values ​​of the Ministry of National Education. The research that the researcher conducted aims to analyze the activities of sunnah worship to increase character values ​​in the Shalafi Islamic Boarding School environment. This research was conducted with descriptive research through a quantitative approach. The results of data processing and analysis show that sunnah prayers and sunnah fasting, on increasing character values ​​in physical education with the results it can be accepted that there is a significant effect. Although based on the calculation of determination, it is known that the increase of 21.2% and 78.8% is influenced by other factors not examined.